Nano Quercetin Accelerates Wound Healing in Laboratory Mice: Nano Quercetin Mempercepat Penyembuhan Luka pada Tikus Laboratorium - Rasha Ali Salman; Amer Talib Tawfeeq; Mohanad W. Mahdi Alzubaidy (Academia Open, 2024)
This study explores the use of Curecetin nanoparticles, synthesized and characterized through X-ray Diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FTIR), and measured using Scanning Electron Microscopy (SEM) with sizes ranging from 13.40 to 44.66 nm. We conducted in vivo experiments on laboratory animals, applying nanoparticle doses of 10 mg, 50 mg, and 100 mg to 30 mm wounds. Skin wounds pose significant medical challenges due to potential complications like rupture and delayed healing. Results indicated that Curecetin nanoparticles significantly accelerated wound healing, with wound size reduction observed as early as the second day and substantial healing by the eighth day, suggesting the potential of nanoparticles in therapeutic applications for skin wounds. Highlights: Precise Characterization: Curecetin nanoparticles were precisely synthesized and characterized using XRD, FTIR, and SEM. Rapid Healing: The study showed that Curecetin nanoparticles significantly accelerated wound healing in laboratory animals. Clinical Potential: Results indicate a promising future for nanoparticle applications in treating skin wounds clinically. Keywords: Nanoparticles, Curecetin, Wound Healing, Nanotechnology, Organism